Friday

August 1, 2014

August 1, 2014

Posted by **Kane** on Monday, October 4, 2010 at 11:38am.

(3x^2+4x-3)^2-(3x^2-x+2)^2

then is it this

(9x^4+24x^3-2x^2-24x+9)-(9x^4-6x^3+13x^2-4x+4)

or this

9x^4+24x^3-2x^2-24x+9-9x^4-6x^3+13x^2-4x+4

should it have brakets or not thats my only problem

thanks

**Related Questions**

algebra - Did I do this problem the correct way if so is there a shorter way to ...

alg2 check? - solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x...

Math - consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (...

math help - 5) Consider the equations: f(X)= -6x-1 and g(x)=4x^2 Select the ...

math help please - 12. (-8x) x (3x^2) -5x^3 -24x^2 -24x^3 -5x^2 13. (-11z)^0 z 1...

MATH - f(x)= -6x-1 and g(x)=4x^2 select the soultion for (f+g)(x) stuck not sure...

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

algebra - -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for ...

algebra - Use polynominal long division to divide -4x^3+24x^2-24x+4 by x^2-5x+1

math - Use polynomial long division to divide -4x^3 + 24x^2 – 24x + 4 by x^2 – ...